Neck, shoulder, and low back pain in adolescence - Auvinen, J. (Juha) (University of Oulu, 2010)
Abstract The etiology of musculoskeletal disorders remains largely unclear, pain being the predominant complaint. The prevalence of neck pain (NP), shoulder pain (SP), and low back pain (LBP) increases drastically during adolescence. Potentially modifiable risk factors of NP, SP, and LBP should be identified at that age. First, this study evaluated the prevalence of NP, SP, LBP and peripheral pains (upper or lower extremities) and the prevalence of multiple pains. Second, the study determined the role of a set of potentially modifiable risk factors for adolescents’ NP, SP, and LBP (physical activity, inactivity, sedentary activities in cross-sectional study design and quantity and quality of sleep in follow-up study design). The study population belongs to the 1986 Northern Finland Birth Cohort (NFBC 1986), consisting of 9,479 children with an expected date of birth between July 1, 1985 and June 30, 1986 in the two northernmost provinces of Finland, Oulu and Lapland. NP, SP, and LBP were common at the ages 16 and 18, while medical consultations for these pains were less frequent. The prevalence of pain increased with age. Peripheral pains were rare. Surprisingly many adolescents reported multiple musculoskeletal pains. Girls were more likely to report pain than boys. Both low and high level of physical activity, some risk sport activities, high amount of sedentary activities, and insufficient quantity and quality of sleep increased the risk of NP, SP, and LBP in adolescence. It may be possible to reduce the occurrence of musculoskeletal pain by having a positive impact on potentially modifiable risk factors, such as physical activity, sedentary activities and sleep hygiene. Therefore, intervention studies focusing on these factors are needed in the future. Tiivistelmä Useimmiten tuki- ja liikuntaelinsairauksien tarkka syy jää epäselväksi ja kipu on niiden pääasiallinen ilmentymä. Niska-, hartia- ja alaselkäkipujen esiintyvyys väestössä nousee merkittävästi teini-iässä. Tämän vuoksi niska-, hartia- ja ...